PERAN SENI MUSIK DALAM PENDIDIKAN MULTIKULTURAL - Desyandri Desyandri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Indonesia is a multicultural state, in which diverse of cultures have spread from Sabang until Merauke, spread across thousands of islands with diverse of cultures. Order was changed with globalization and the development of Science, Technology, and the Arts (IPTEKS). Globalization also has an impact on inequality, and injustice in the world of education. Educationin generalis a giftof knowledge, experienceandskillsto the studentsso as toform apositive attitudeandbe able tobuild anoblecharacterin order to formthe nation withregardthe values​​of cultural diversity. MusicArteducationprovides the knowledge, experience, andcompetencethroughfivebasic components, namely: expression, appreciation, creation, harmony, andbeautyareintegratedwithMulticulturalEducation. Thisarticledescribes theroleof musicinmulticulturaleducationisto fosterawarenessand concernin establishinga multiculturallearningcommunityinschools.